2023
DOI: 10.1002/uog.24976
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of ultrasound signs for detecting adnexal torsion: systematic review and meta‐analysis

Abstract: What are the novel findings of this work?Quality of studies assessing the role of different ultrasound signs for diagnosing adnexal torsion was moderate. There is significant heterogeneity among studies.Therefore, investigating this unique clinical issue using meta-analysis might lead to erroneous conclusions as to the diagnostic capabilities of sonographic signs in the diagnosis of adnexal torsion. What are the clinical implications of this work?This meta-analysis shows the current evidence about the role of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 37 publications
(336 reference statements)
0
2
0
Order By: Relevance
“…Một nghiên cứu tổng quan và phân tích hệ thống khác được thực hiện năm 2022, ghi nhận kết quả như sau: Bảng 1: Giá trị của các dấu hiệu xoắn trên siêu âm [11] Độ nhạy (sensitivity)…”
Section: Tóm Tắt Bệnh áNunclassified
“…Một nghiên cứu tổng quan và phân tích hệ thống khác được thực hiện năm 2022, ghi nhận kết quả như sau: Bảng 1: Giá trị của các dấu hiệu xoắn trên siêu âm [11] Độ nhạy (sensitivity)…”
Section: Tóm Tắt Bệnh áNunclassified
“…Ultrasound is the gold standard for ovarian cyst torsion; it eliminates differential diagnosis and identifies factors that may favor torsion, such as cyst visualization. According to the literature, the ultrasound signs that may suggest the diagnosis of adnexal torsion are: ovarian edema, adnexal mass, whirlpool sign, absent ovarian Doppler flow, pelvic fluid [5]. However, ultrasound exploration of the adnexa is difficult during pregnancy because of the increased size of the uterus and the retro-uterine position of the adnexa during pregnancy, especially during the second and third trimesters.…”
Section: Introductionmentioning
confidence: 99%
“…To confirm the diagnosis, pelvic ultrasound with or without Doppler flow analysis is widely used 4. However, its contribution is low, with a sensitivity ranging from 46% to 73% depending on the study and recently confirmed by a meta-analysis 5 6. Other imaging techniques have been considered, such as MRI, with much greater sensitivity than ultrasound.…”
Section: Introductionmentioning
confidence: 99%